Parathyroid carcinoma in chronic renal disease – a case series of three patients and review of literature. Issue 2 (4th March 2023) - Zivaljevic, Vladan; Zivic, Rastko; Slijepcevic, Nikola; Buzejic, Matija; Dundjerovic, Dusko; Trbojevic Stankovic, Jasna; Stojakov, Dejan; Jovanovic, Milan; Paunovic, Ivan
Abstract: Background: Apart from being a rare endocrine tumor, parathyroid carcinoma is also one of the rarest malignancies in human beings. Parathyroid carcinoma is even more uncommon in haemodialysis patients with end-stage renal disease. The pathogenesis of parathyroid hyperplasia in haemodialysis patients is well known, but the mechanism of development of parathyroid carcinoma in these patients remains unclear. Methods: Three cases of parathyroid carcinoma in haemodialysis patients are presented in this study: a 69-year-old male patient and two female patients (67 and 61 years old). In all cases parathyroid carcinoma infiltrated the ipsilateral thyroid lobe and in one patient the right laryngeal nerve was involved as well. One patient underwent three surgical procedures. Results: After surgical treatment, all patients were normocalcaemic and showed a significant reduction in PTH levels. Conclusion: In patients with secondary hyperparathyroidism, who develop parathyroid carcinoma, surgical resection is the only viable treatment option.